Geographical distribution of land use problems in date palm cultivation in Baghdad Governorate - Kadhim, Sherin Amad; Kadhim, Dalal Hassan (Al-Adab Journal, 2021)
The decline of the areas planted with palms, their numbers and production in Baghdad governorate is due to many natural, human and life factors. The research aims to study the geographical distribution of the problems and obstacles facing date palm cultivation in Baghdad Governorate and the reasons behind them. And a statement of the geographical distribution of date palm cultivation in terms of areas, numbers, production and productivity for the year 2018 by administrative units (districts). A questionnaire form was created with (500) questionnaires containing 17 questions related to date palm problems and their obstacles, as well as conducting a field study and approving data issued by official departments in conducting the research, As the area of palm trees in the governorate of Baghdad reached 96,809 dunums and its number is 2420225 trees, while production reached 148050 tons. The data related to the geographical distribution of date palm cultivation and the problems and obstacles that they suffer from were enumerated and classified as categories according to the Natural Breaks Jenks method and represented on maps using the ARC GIS 9.3 software. . The most important findings of the research are the outweighing of human factors in the decline of date palm areas, the most prominent of which is urban expansion by 64%, followed by the problem of lack of government support by 55%, followed by the life factors represented by the problem of pests and diseases by 63%. Natural factors were followed by 42% of the total owners of orchards, followed by saline land, at 35%.